Corn mice (Calomys musculinus) movement in linear habitats of agricultural ecosystems - Sommaro, Lucía Valeria (2010)
Movement patterns of Calomys musculinus in linear habitats were studied in relation to sex, season, year, abundance, and width of border. Movement distances (MDs) were measured by seasonal capture, mark, and recapture samples during 2 years in wide and narrow borders in agroecosystems. The smallest MDs were registered in autumn and the highest in spring. In the breeding period MDs of males were larger than those of females. In the nonbreeding period MDs were similar between sexes. Effects of sex on MD were consistent with the promiscuous mating system of C. musculinus. MDs were greater in narrow than in wide borders. The narrowness of suitable habitats would force the mice to extend foraging trips in narrow borders. Opportunistic behavior of C. musculinus allows it to use linear habitats in a similar way to the 2-dimensional natural habitats.